What does language assessment literacy mean to teachers?. (9th February 2019) - Berry, Vivien; Sheehan, Susan; Munro, Sonia
Abstract: Language assessment literacy has been discussed by language assessment specialists since Davies' seminal 2008 article. Much of this discussion has focused on experts' opinions of what teachers know, do not know, and should know about assessment. This paper reports on a project which aimed to put teachers at the centre of the debate by exploring their attitudes to assessment and their assessment practices. Interviews, classroom observations with follow-up interviews, and focus group discussions were held with teachers based in the United Kingdom, France, and Spain. The teachers discussed their training in assessment and their attitudes towards it. Although many of them expressed a lack of confidence in their knowledge of the subject, the teachers we observed in fact successfully deployed a wide range of assessment techniques. However, they tended to characterize these as teaching activities and, therefore, part of good teaching practice. Testing and grading were viewed negatively.